(untitled) (Global Media Journal - German Edition, 2015)
While the use of monitoring and evaluation (M&E) by media development implementers is well documented, organizations’ coping strategies to adapt to new environments in media and development still remain a relatively unexplored area. The article aims at showing how the theoretical lessons learnt by the industry have been put into practice and how a successful change can be driven within an organization using outside experts. A results-oriented culture of performance and service has been enforced since the 1990s in the EU. Evaluation systems have been a powerful catalyst in driving the transition from media support to media development and in making the latter more independent from broadcasters and donors. In recent years, changes in media assistance procedures and aims have profoundly modified the traditional landscape. This article will not question these changes, their origin and motivations. It will focus on implementers’ coping strategies to adapt (or not) to these new procedures and aims and how results-oriented evaluations can drive the shift from outputs to outcomes in a changing media development sector. Can capitalizing on experience be considered a learning process that prepares for change and improves the design and implementation of projects? To what extent can it help to empower the operator as an organization? Referring to various concrete case studies from British, French and German media assistance, the article will focus on virtuous change – the circumstances that encourage structures, as well as donors who fund them, to better define and operationalize their strategies.